EVALUASI PROGRAM LAYANAN RAKYAT UNTUK SERTIFIKASI TANAH (LARASITA) DI KABUPATEN KAMPAR - Rudy Irawan; Febri Yuliani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Land is a place for people to exercise their nature as personal and social. Land ownership must be clearly evidenced by a legally registered land title certificate called a land certificate. Certificate of land is very necessary in the order of land administration. To improve the service to the public in the certification of land and in order to bring about the implementation of duties and functions, BPN Kabupaten Kampar carried out the mandate of BPN RI based on the regulation of Head of BPN number 18 Year 2009 to society developed land services called Larasita (People's Service for Land Certification). Still less people in the management of certificates through Larasita and the lack of services received in various regions attracted writers to conduct research titled Evaluation of People Services Program for Land Certification (LARASITA) in Kampar District. In Dunn's theory, there are 6 (six) evaluation indicators, namely: e.factivity, efficiency, adequacy, equity, responsiveness, and policy accuracy. Research method used is descriptive qualitative with purposive sampling technique. Informants in this study were Head of Controlling Section and Empowerment of BPN Kabupaten Kampar, Chief of Larasita, Larasita Secretary, Larasita Member, District Siak Subdistrict Siak Hulu District, Kampar Left and Bankinang Subdistrict, Kades Tanah Merah, Subdistrict River Hope, District Governance Sand Sialang Subdistrict From the results of qualitative descriptive data analysis from the side of the evaluation, the Service Program for Land Certification (Larasita) in the district of Kampar is categorized as yet to be successful. This is evident from the unreachable goals and objectives of the Program. In addition, there are also factors that influence policy evaluation, namely: Lack of Socialization, Lack of Human Resources and Operational Budget, lack of mobilizing vehicles and frequent interruption of communication devices and presuption Community about this program.Keywords: Evaluation, Land, Service, Larasita